Marion Butler and American Populism - Hunt, James L. (James Logan), 1959- (University of North Carolina Press, 2003)
Exploring the life and leadership of Marion Butler, James Hunt offers insight into the challenge of American reform politics. He served in the US Senate and was a crucial figure in the Populist Party. In this account, Hunt seeks to show how strongly Butler believed in Populist principles.